From Roman Britain to Norman England - Sawyer, P. H. (Routledge, 1998)
This revised edition of the classic text of the period provides both the student and the specialist with an informative account of post-Roman English society. After a general survey of the main developments from the fourth century to the eleventh, the book offers analysis of:* social organization* the changing character of kingship, of royal government and the influence of the church* the history of settlement* the making of the landscape* the growth of towns and trade* the consequences of the Norman Conquest. The author also considers the various influences; Brit.